“Ode on a Grecian Urn” and Browning’s “A Toccata of Galuppi’s” - Hawlin, Stefan (Romanticism and Victorianism on the Net, 2012)
This essay identifies and explores the intertextual relationship between Browning’s crucial mid-career poem, “A Toccata of Galuppi’s,” and Keats’s “Ode on a Grecian Urn,” affirming the latter as the crucial inter-text for the former. “A Toccata of Galuppi’s” is revealed as a metatextual commentary, providing an interesting mid-nineteenth-century perspective on Keats’s ode, where we can see aspects of the tension in Browning’s sensibility between “Hebrew” and “Hellene” playing themselves out.